PERATURAN DAERAH KABUPATEN BUNGO NOMOR 15 TAHUN 2007 DALAM MENGATASI PATOLOGI SOSIAL DI KABUPATEN BUNGO - Pratiwi, Widya (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2019)
This article stems from an increase in cases of prostitution (Social Pathology) from 2013, which amounted to 75 people and increased in 2017 to 87 people, using descriptive methods and qualitative approaches. Data collection techniques used were interviews with 10 informants. The results of the research on the implementation of Bungo District Regulation No. 15 of 2007 concerning the Eradication of Prostitution in Bungo District carried out by the Office of the Civil Service Police Unit and the Bungo Regency Fire Department are still not going well. , massage venues, dim cafes, and nightclubs (discos) in hotels. Keywords: Social Pathology, Prostitution, Regional Regulation No.15 of 2007, Bungo